Benzophenone constituents from the roots of Garcinia eugenifolia - Jong, Vivien Yi Mian; Ee, Gwendoline Cheng Lian; Md. Sukari, Mohd Aspollah; Yap, Taufiq Yun Hin; Khong, Heng Yen; Chan, Margaret Kit Yok (International Congress of Chemistry and Environment, 2012)
Our recent phytochemical investigation on the roots of Garcinia eugenifolia gave a new benzophenone,( 3,4-dihydroxyphenyl)(3-hydroxy-5-methoxyphenyl) methanone(1), one other benzo-phenone,(3- hydroxy-phenyl)3,4,5-trihydroxyp- henyl) methanone (2), together with four triterpenoids, magniferolic acid (3), euphadienol(4), β-sitosterol (5) and friedelin (6) as well as two xanthones, 5,9-dihydroxy-8-methoxy- 2,2-dimethyl-7-(3-methylbut-2-enyl)Pyrano[3, 2-b] xanthen- 6(2H)-one(7)and1,3,6,8-tetrahyd roxyxant-hone (8).The structures of these compounds were fully characterised by NMR spectroscopic analysis.